Management of Soil Resources for Sustainable Development under a Changing Climate - Jahangir, MMR; Jahan, I; Mumu, NJ (Journal of Environmental Science and Natural Resources, 2019)
Development was conventionally driven by one particular need, without fully considering the wider or future impacts. This kind of approach has now been considered to be responsible for the economic and environmental catastrophes that humans are facing: from large scale financial crises caused by irresponsible banking to the changes in global climate resulting from our dependence on fossil fuel based energy sources. Soils provide essential ecosystem services such as primary production, regulation of biogeochemical cycles (with consequences for the climate), water filtration, resistance to diseases and pests, and regulation of above-ground biodiversity. Changing of the climate systems is unequivocal. Adaptation to global climate change through improved soil quality by adoption of improved management practices is key to maintaining sustainable agricultural production. A holistic approach to soil management as the engine for increasing productivity by increasing resource use efficiency and making agriculture environmentally compatible is more important than ever before. Strategies of greenhouse gas emission reduction include those that increase the use efficiency of inputs. Herein, we discussed how management and protection of soil resources can contribute to sustainable development through sustainable agricultural production while maintaining sustenance of soil fertility. J. Environ. Sci. & Natural Resources, 11(1-2): 159-170 2018